TNF‐α augments CXCR2 and CXCR3 to promote progression of renal cell carcinoma. Issue 11 (14th June 2016) - Sun, Kuang‐Hui; Sun, Guang‐Huan; Wu, Yi‐Ching; Ko, Bai‐Jiun; Hsu, Hui‐Tzu; Wu, Sheng‐Tang
Abstract: Within the tumour microenvironment, a complex network of chemokines and their receptors affects the initiation and progression of tumours. The higher levels of tumour necrosis factor‐alpha (TNF‐α) are associated with tumour progression and an anti‐TNF‐α monoclonal antibody has been used successfully to treat patients with renal cell carcinoma (RCC). However, the role of chemokines and their receptors in the TNF‐α‐promoted progression of RCC remains unclear. In this study, TNF‐α was found to enhance the migration, invasion and epithelial‐mesenchymal transition (EMT) of RCC cells. To further investigate the molecular mechanism of TNF‐α on the progression of RCC, reverse transcription and quantitative PCR was used to screen chemokines and chemokine receptors that were associated with tumorigenesis. The results showed that TNF‐α significantly increased the expressions of CXCR2 and CXCR3 and their related ligands in RCC cells. Subsequently, we used a lentiviral shRNA system to knockdown the expression of CXCR2 and/or CXCR3 in RCC cells. CXCR2 and CXCR3 silencing inhibited the induction of Slug and ZEB‐1 with TNF‐α treatment of RCC cells. In addition, the knockdown of both CXCR2 and CXCR3 resulted in a greater decrease in cell migration, invasion and clonogenic ability compared with either CXCR2 or CXCR3 knockdown alone. Moreover, CXCR2 and CXCR3 silencing significantly reduced the sphere‐forming ability of RCC cells. High expression levels of CXCR2 and CXCR3 in cancer tissues correlated with tumour progression of renal cell carcinoma. These findings suggest that TNF‐α augments CXCR2 and CXCR3 to promote the progression of renal cell carcinoma leading to a poor prognosis.